Optimal irrigation strategies for watermelon crop - Júnior, Aderson Soares de Andrade; Frizzone, José Antonio; Bastos, Edson Alves; Cardoso, Milton José; Rodrigues, Braz Henrique Nunes (Pesquisa Agropecuaria Brasileira, 2001)
This paper aimed to determine optimal strategies for irrigation management watermelon crop (Citrullus lanatus Thumb. Mansf.), when water is limiting resource under different values of the crop and electrical energy price. The analysis involved quadratic production function and linear cost function developed to the soil and climate characteristics of the Coastal Tablelands, at Piauí State, Brazil. The highest net incomes were achieved with deficit irrigation, in the range crop prices of the US$ 0.05 kg-1 to US$ 0.35 kg-1, independently of electrical energy price. Up this range, irrigation depth that maximizes fruits yield must be used.